The Hiukitak School of Tuktu: Collecting Inuit Ecological Knowledge of Caribou and Calving Areas Through an Elder-Youth Camp - Thorpe, Natasha L. (ARCTIC, 1998)
. this paper is the first formal report of the elder-youth camp recently held at the Hiukitak River near Bathurst Inlet in the Kitikmeot region. I begin by providing a background on the methods used in developing the project, focusing on how the research and research team developed, and why the camp became a key component of the methods. Next, I show how a camp can be a reliable, effective and fun way to record and communicate Inuit ecological knowledge (IEK). Throughout this section, I explore gender-related differences in expertise about caribou. .